2021
DOI: 10.1016/j.radcr.2021.04.057
|View full text |Cite
|
Sign up to set email alerts
|

The liver twist: A case of accessory liver lobe torsion presenting after mild trauma

Abstract: An accessory liver lobe is a congenital anomaly of hepatic tissue most commonly due to embryonic heteroplasia. Rarely, accessory liver lobes can undergo torsion and present as an acute surgical emergency. Although common in certain animals, there are only a few reported cases of accessory lobe torsion in humans. We report a multi-modality radiographic diagnosis of an acute torsion and subsequent infarct of an accessory liver lobe following minor trauma in a 29-year old male patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, radiologic changes from hepatobiliary involvement are often not seen until disease progression. 3,4,[6][7][8] In this case, the patient was noted to have biliary tree dilation by ultrasound and splenomegaly with thrombocytopenia thought to be from splenic sequestration, indicating hepatic involvement. Despite hepatic involvement, hepatic synthetic function was normal as indicated by normal INR, thus excluding liver dysfunction or coagulopathy as an etiology of the patient's intra-abdominal bleeding.…”
Section: Discussion Of Case and Literaturementioning
confidence: 76%
See 1 more Smart Citation
“…However, radiologic changes from hepatobiliary involvement are often not seen until disease progression. 3,4,[6][7][8] In this case, the patient was noted to have biliary tree dilation by ultrasound and splenomegaly with thrombocytopenia thought to be from splenic sequestration, indicating hepatic involvement. Despite hepatic involvement, hepatic synthetic function was normal as indicated by normal INR, thus excluding liver dysfunction or coagulopathy as an etiology of the patient's intra-abdominal bleeding.…”
Section: Discussion Of Case and Literaturementioning
confidence: 76%
“…9,10,19 Patients with hepatic torsion are at risk for hepatic infarct, hepatic rupture, hemangioma, biliary obstruction, colonic obstruction, and gallbladder torsion. [8][9][10][11][12] Symptoms concerning for further complication from hepatic torsion should be monitored following suspected diagnosis and include new-onset abdominal pain, nausea, vomiting, anorexia, pallor or decreased hemoglobin secondary to hypovolemic shock, impairment of liver function reflected in labs, and cholestasis reflected in stool quality and labs. 20 Otherwise, asymptomatic occurrences should only be excised if the liver lobe is pedunculated or in close proximity to either the cystic duct or common bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…MRI indicates superior diagnostic value to CT, as the vascular system extending from the healthy liver through the stalk into the giant AHL is more likely to be detected by dynamic contrast-enhanced MRI ( 2 ). However, it has been suggested that for complete stalk torsion, a contrast enhancement CT scan, especially CTA, is more useful than ultrasonography for diagnosis ( 14 ). Ultrasonography, plain CT scan, and MRI have also been reported to be non-specific for diagnostic imaging findings in pediatric AHL patients ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A history of trauma and surgery involving the abdominal wall with the new development of acute symptoms such as abdominal pain in patients with an accessory liver lobe should highly suggest liver torsion. This should subsequently allow for a rapid transition to surgery to attempt to repair the torsion with the segments that probably become ischemic [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, CT scan and CTA are the primary choices of imaging modality to evaluate liver lobe torsion. These tools increase the likelihood of appropriate diagnoses and increases the possibility of restoring health to the ischemic lobe or segment [1]. The clinical signs of hepatic lobe torsion may vary, with some cases being either subclinical or resulting in death.…”
Section: Introductionmentioning
confidence: 99%